2017
DOI: 10.1016/j.ijrobp.2017.06.2174
|View full text |Cite
|
Sign up to set email alerts
|

Online Advertising and Marketing Claims by Providers of Proton Beam Therapy: Are They Guideline Based?

Abstract: Purpose/Objective(s): To correlate parameters derived from apparent diffusion coefficient (ADC) volumes associated with the changes in specified abnormal white matter (WM) to overall survival (OS) following therapies in glioblastoma (GBM). The unsupervised machine learning was designed to reduce uncertainties on a relatively small size data for a prediction model. Materials/Methods: The study employed 41 GBM patients treated with radiotherapy (60 Gy) followed by Temozolomide. The ADC ranges for normal WM and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…Although the internet may contain useful health information, the quality of many websites is unregulated. [14][15][16][17][18][19]22,45,46 Perhaps ironically, peer-reviewed medical information, such as in the form of journal articles or society guidelines, may be financially restricted and therefore not easily accessible to the general population. Given that misinformation or inappropriate interpretation of information may impact health-related choices among patients with cancer, [23][24][25] our finding of increasing healthspecific internet use among cancer survivors with later year of survey underscores the value of improving the quality of health information websites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the internet may contain useful health information, the quality of many websites is unregulated. [14][15][16][17][18][19]22,45,46 Perhaps ironically, peer-reviewed medical information, such as in the form of journal articles or society guidelines, may be financially restricted and therefore not easily accessible to the general population. Given that misinformation or inappropriate interpretation of information may impact health-related choices among patients with cancer, [23][24][25] our finding of increasing healthspecific internet use among cancer survivors with later year of survey underscores the value of improving the quality of health information websites.…”
Section: Discussionmentioning
confidence: 99%
“…12 Although medically sponsored websites with evidencebased guidelines exist, the internet can also serve as a platform for dissemination of potentially harmful medical misinformation. 11,13 Studies regarding the quality of online health information in oncology [14][15][16][17] and other fields 18,19 have shown the accuracy of such pages to be variable, with many online resources with poor-quality information garnering high-volume readership. 20 In addition, commercial websites, some of which are run by companies that pay to rank themselves among the top hits for healthrelated searches, 18 may provide information biased toward the use of particular products or treatments.…”
Section: Introductionmentioning
confidence: 99%
“…For men with prostate cancer, proton therapy treatment plans typically reduce the radiation dose to the rectum, bladder, and other nontarget normal pelvic tissues relative to photon-based EBRT using intensity-modulated radiotherapy (IMRT), 7 although singleinstitution retrospective studies have not identified a measurable difference in physician-assessed acute or late toxicities. 8,9 While proton therapy represents a small percentage of radiation therapy treatments for prostate cancer and remains a relatively scarce resource, the growth in proton therapy from approximately 2% to 5% of EBRT cases between 2004 to 2012, 10 the increased cost of treatment, 11 the increasing number of proton centers, the sometimes questionable marketing claims, 12 and the lack of randomized data demonstrating its superiority to alternative treatments for prostate cancer have underscored the scrutiny this treatment modality continues to receive. Previous population-based analyses from the Surveillance, Epidemiology, and End Results (SEER) database, a linked SEER-Medicare analysis, and the MarketScan Commercial Claims and Encounters database have reached conflicting conclusions about the acute and late toxicity profile of proton therapy relative to IMRT.…”
Section: Introductionmentioning
confidence: 99%
“…Поэтому миф, что протоны эффективнее и безопаснее -всего лишь миф, но становящийся религией. По данным постера, представленного на ASCO 2019 канадскими авторами [52], вебсайты центров протонной терапии вводят больных в заблуждение, утверждая, что протоны повышают шанс излечивания (61 % утверждений), минимизируют осложнения (85 %) и приводят к улучшению качества жизни (39 %).…”
Section: тимур митин: станет ли вскоре вся лучевая терапия протонной?unclassified